Pterostilbene on Metabolic Parameters: A Randomized, Double-Blind, and Placebo-Controlled Trial. (25th June 2014) - Riche, Daniel M.; Riche, Krista D.; Blackshear, Chad T.; McEwen, Corey L.; Sherman, Justin J.; Wofford, Marion R.; Griswold, Michael E.
Abstract : Introduction . The purpose of this trial was to evaluate the effect of pterostilbene on metabolic parameters. Methods . A prospective, randomized, double-blind, and placebo-controlled study that enrolled 80 patients with a total cholesterol ≥200 mg/dL and/or LDL ≥ 100  mg/dL. Subjects were divided into four groups: (1) pterostilbene 125 mg twice daily; (2) pterostilbene 50 mg twice daily; (3) pterostilbene 50 mg + grape extract (GE) 100 mg twice daily; (4) matching placebo twice daily for 6–8 weeks. Endpoints included lipids, blood pressure, and weight. Linear mixed models were used to examine and compare changes in parameters over time. Models were adjusted for age, gender, and race. Results . LDL increased with pterostilbene monotherapy (17.1 mg/dL; P = 0.001 ) which was not seen with GE combination (P = 0.47 ). Presence of a baseline cholesterol medication appeared to attenuate LDL effects. Both systolic (−7.8 mmHg; P < 0.01 ) and diastolic blood pressure (−7.3 mmHg; P < 0.001 ) were reduced with high dose pterostilbene. Patients not on cholesterol medication (n = 51 ) exhibited minor weight loss with pterostilbene (−0.62 kg/m 2 ; P = 0.012 ). Conclusion . Pterostilbene increases LDL and reduces blood pressure in adults. This trial is registered with Clinicaltrials.gov NCT01267227 .